PENGARUH ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Calen Calen; Beatrice Nathania (Politeknik Bisnis Indonesia, 2024)
This study aims to determine the effect of Economic Value Added and Market Value Added to Return shares in manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The data collection method used is secondary data. The data used is in the form of company financial report data which can be accessed through www.idx.co.id. The sampling technique uses the method purposive sampling. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period, totaling 193 companies. Sampling technique by method purposive sampling, based on the objectives of the researchers using certain criteria, the total sample obtained was 40 companies. The results of the t test research show that Economic Value Added no effect and not significant to Return shares; Market Value Added no effect and not significant to Return share. F test shows that Economic Value Added and Market Value Added simultaneously have no effect on Return shares.